Methodology of the research of the conflation in the Epistle to Galatians - Taras Dyatlik (Cхід)
The article is devoted to the study of theological methodology of the phenomenon of conflation in the text of the Epistle to Galatians. The issue of conflation was earnestly introduced into the field of New Testament textual criticism by Westcott and Hort in the late nineteenth century. Conflation is always the longest variant that is tertiary in origin and consists of the primary (authentic reading) and secondary (secondary variant) simpla. There is a set of the variants which seem to have appeared on account of such possible reasons as doctrinal alteration or harmonization, or syntactical improvement. In the tentative analysis of the candidates for conflation, the eight longest variant readings from the Epistle to Galatians are examined according to the methodology described in the introductory part of the investigation, so as to find out whether they can be regarded as conflations, difflations, or variants which emerged by "addition and omission".